2008
DOI: 10.2139/ssrn.1328192
|View full text |Cite
|
Sign up to set email alerts
|

India's Bond Market - Developments and Challenges Ahead

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Another huge advancement was the presentation of the Market Stabilization Scheme which has extended the instruments accessible to the Reserve Bank for dealing with the surplus liquidity in the framework. These changes can be momentarily seen as an efficient exercise for the improvement of the debt market just as reconciliation of the whole financial markets by making it profound, wide and transparent [8]. In glancing back at the succession and speed of these changes that have been set up longer than 10 years, one starts to value the complexity and difficulty that is characteristic for the advancement of a productive debt market we actually have far to go.…”
Section: Corporate Bond Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…Another huge advancement was the presentation of the Market Stabilization Scheme which has extended the instruments accessible to the Reserve Bank for dealing with the surplus liquidity in the framework. These changes can be momentarily seen as an efficient exercise for the improvement of the debt market just as reconciliation of the whole financial markets by making it profound, wide and transparent [8]. In glancing back at the succession and speed of these changes that have been set up longer than 10 years, one starts to value the complexity and difficulty that is characteristic for the advancement of a productive debt market we actually have far to go.…”
Section: Corporate Bond Marketmentioning
confidence: 99%
“…While banks were permitted to utilize futures just to fence their G-sec investments in Held for Trading (HFT) and Available for Sale (AFS) classes, PDs were permitted to interest rate derivatives (IRDs) for both hedging and trading. Nonetheless, because of the absence of liquidity of the exchange traded futures market, Securities and Exchange Board of India (SEBI) in meeting with FIMMDA improved on futures contracts on a 10-year notional bond, which is evaluated based on the Yield To Maturity' (YTM) of a bushel including three securities with development going from 9 to 11 years [9]. The exchanges are currently dispatching another product.…”
Section: Interest Rate Futures (Irfs)mentioning
confidence: 99%
“…The bond market's key aim is to provide creditors with a safe stream of income against uncertain stock market. (Schou-Zibell & Wells, 2008) identified that the Indian financial system is rapidly evolving, characterized by fast economic growth, healthier economies and even greater performance.…”
Section: The Relationship Between Bond Market and Economic Growthmentioning
confidence: 99%
“…In India, the challenge of obtaining long-term funding for the infrastructure sector is greater due to the absence of a well-developed bond market. While the government bond market is illiquid, the corporate bond market is restrictive to participants and is mostly arbitrage-driven (Schou-Zibell and Wells, 2008). Problems relating to information asymmetry, low liquidity and distortions from the corporate debt segment would need to be solved to broad base the debt markets (Bose and Coondoo, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%